2007
DOI: 10.1177/0148607107031004278
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Amino Acid and Metabolic Acidosis in Premature Infants

Abstract: OBJECTIVE: Aggressive parenteral nutrition including amino acids is recommended for low birth weight infants to prevent energy and protein deficit. Their impact on acid-base homeostasis has not been examined. PATIENTS AND METHODS:We investigated the impact of dose and duration of parenteral amino acids, with cysteine, on acid-base parameters in 122 low birth weight infants. Premature infants <32 weeks, <1850g and receiving parenteral amino acids at 1.5g·kg -1 ·d -1 for an extended period (>24h), or 3g·kg -1 ·d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 23 publications
3
24
0
3
Order By: Relevance
“…Moreover, the incidence of patent DA does not appear to be augmented in the preterm newborns exposed to permissive hypercarbia [40] . On the other side, respiratory acidosis requiring increased ventilator rates and peak airway pressures is frequently observed in infants with patent DA [1,2] , and it has been reported that a correlation between metabolic acidosis and large patent DA exists [7] . In the present study, we demonstrated that clinically accepted acidosis produces significant relaxation of the DA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the incidence of patent DA does not appear to be augmented in the preterm newborns exposed to permissive hypercarbia [40] . On the other side, respiratory acidosis requiring increased ventilator rates and peak airway pressures is frequently observed in infants with patent DA [1,2] , and it has been reported that a correlation between metabolic acidosis and large patent DA exists [7] . In the present study, we demonstrated that clinically accepted acidosis produces significant relaxation of the DA.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory and metabolic acidosis are frequent events in the clinical course of very preterm infants [1][2][3][4][5][6][7] . Changes in pH can have a profound influence on pulmonary and systemic vascular resistance, and on the reactivity of the vessels to agonists.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous study from Ridout et al showed no relationship between BUN and amino acid intake [15]. Jadhav looked at the relationship between metabolic acidosis and amino acid intake but did not find a correlation [16]. There is no scientific reason to explain why VLBW infants should not be offered 3 to 3.5 g/kg/d of amino acids immediately after birth.…”
Section: Discussionmentioning
confidence: 96%
“…Современные данные, оценивающие аминокислот-ный состав парентерального питания, свидетельствуют о том, что аминокислоты могут быть быстро введены без метаболических нарушений даже у больных детей, не вызывая ацидоз [41,42]. Необходимо подобрать такое количество белка, которое позволит избежать его большего дефицита, который обычно возникает в 1-ю нед жизни новорожденного.…”
Section: вопросы современной педиатрииunclassified